What we can and can't afford essays on Vietnam, patriotism and American life - Ehrhart, William D. 1948- (McFarland & Company, Inc., 2023)
Bill Ehrhart's experiences in the Vietnam War have defined his life--first as an enlisted member of a Marine infantry battalion, then as an author, poet and teacher who has spent fifty years explicating the war and its consequences in books, lectures and interviews. In these essays he explores a diverse range of topics. They include gun violence and the Second Amendment, American politics and the accelerating destruction of civil society, Afghanistan and other foreign policy misadventures, Israel and Palestine, the nature of patriotism, history as fact and mythology, the blessings of technology, the vast mystery of the universe, the attraction of Grand Tour bicycle racing, the much misunderstood writer Stephen Crane, poets you should know about but probably don't. And more. --